The use of mesenchymal stromal cells in treatment of lung disorders. (March 2017) - Kardia, Egi; Zakaria, Norashikin; Sarmiza Abdul Halim, Nur Shuhaidatul; Widera, Darius; Yahaya, Badrul Hisham
The therapeutic use of mesenchymal stromal cells (MSCs) represents a promising alternative clinical strategy for treating acute and chronic lung disorders. Several preclinical reports demonstrated that MSCs can secrete multiple paracrine factors and that their immunomodulatory properties can support endothelial and epithelial regeneration, modulate the inflammatory cascade and protect lungs from damage. The effects of MSC transplantation into patients suffering from lung diseases should be fully evaluated through careful assessment of safety and associated risks, which is a prerequisite for translation of preclinical research into clinical practice. In this article, we summarize the current status of preclinical research and review initial MSC-based clinical trials for treating lung injuries and lung disorders.